Interview with Claudia Beltrão da Rosa: notes on Ancient History research in Brazil - Rosa, Claudia Beltrão da (Romanitas - Revista de Estudos Grecolatinos, 2016)
Interview with Claudia Beltrão da Rosa.
Keywords: Interview; Claudia Beltrão da Rosa; Ancient History research